Analysis for channel capacity of BPSK-based optical wireless communication system - CHEN Jun; HUANG De-xiu; YUAN Xiu-hua (Tongxin xuebao)
The atmospheric turbulence intensity is analyzed by the Γ model based on the theory of information,and the channel capacity of optical wireless communication system based BPSK is calculated by Monte Carlo integral,the detailed analysis of the channel capacity versus the signal-noise-rate（SNR） in different turbulence intensity is given,it is a key theoretical basis for the designs of optical wireless communication.